Bezirk Charkov, Ukraine: Die Infrastruktur im Gebiet der Dnepr-Severskij Donec-Wasserscheide in spätrömischer Zeit und zu Beginn der Völkerwanderungszeit - Schultze, Erdmute (e-Forschungsberichte des DAI, 2023)
The research in the modern district of Kharkiv (East Ukraine) devoted to settlement history of the 4th and 5th century AD in this area has been continued in 2014. The investigations were focused on analyzes of the data and publication of the first results. Based on the surveys of the past few years the distribution of Chernyakhov culture could be recorded more exactly. In Voitenki, an archaeological complex of the Chernyakhov culture, excavations were conducted by the co-operation partner. They brought to light a pottery kiln in the settlement and a number of graves on the cemetery where now 206 graves are known.